2012
DOI: 10.1021/nl301035x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Surface Carrier Dynamics in the Topological Insulator Bi2Te3

Abstract: We discuss the ultrafast evolution of the surface electronic structure of the topological insulator Bi(2)Te(3) following a femtosecond laser excitation. Using time and angle-resolved photoelectron spectroscopy, we provide a direct real-time visualization of the transient carrier population of both the surface states and the bulk conduction band. We find that the thermalization of the surface states is initially determined by interband scattering from the bulk conduction band, lasting for about 0.5 ps; subseque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

22
192
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(215 citation statements)
references
References 30 publications
22
192
1
Order By: Relevance
“…We average the intensity over a narrow energy window (less than 20 meV), and this provides us with a precise information on the energy dependent temporal evolution of the excited electrons. This constitutes an important difference to a previous study on Bi 2 Te 3 , in which large energy windows were selected, enclosing distinct bands [32]. The dynamics is fast for E >> µ (-6-), and apparently slows down when approaching µ (-4-and -3-).…”
mentioning
confidence: 71%
“…We average the intensity over a narrow energy window (less than 20 meV), and this provides us with a precise information on the energy dependent temporal evolution of the excited electrons. This constitutes an important difference to a previous study on Bi 2 Te 3 , in which large energy windows were selected, enclosing distinct bands [32]. The dynamics is fast for E >> µ (-6-), and apparently slows down when approaching µ (-4-and -3-).…”
mentioning
confidence: 71%
“…At fixed energy, the population decay directly reflects the lifetimes and decay rates. As a result, we observe single scattering events at these delays rather than the dynamics of a hot electron gas, which most previous studies on electron dynamics in TIs have focused on [5][6][7]. The dynamics can be described by a rate-equation model.…”
mentioning
confidence: 80%
“…Time-resolved photoemission measures the transient population of initially empty electronic states following an optical pump pulse, and therefore allows us to access electron dynamics directly in the time domain. Previous studies have focused on carrier cooling in bismuth chalcogenides which are intrinsically n type [5][6][7] and can be p doped by Mg [8]. These studies showed that the electron dynamics of TSSs is dominated by the bulk conduction band, but did not provide scattering rates between TSS and the conduction or valence band.…”
mentioning
confidence: 99%
“…Once the dressing field of the pump pulse disappears (t > 500 fs), the sidebands disappear, leaving a heated Dirac cone. The dynamics of this non-equilibrium heated distribution of electrons has been discussed in a number of Tr-ARPES experiments [25][26][27][28] . Here we will focus on the Tr-ARPES spectra taken at t = 0 to ascertain the relative contribution of Floquet-Bloch and Volkov states.…”
mentioning
confidence: 99%